2010
DOI: 10.1016/j.jad.2009.06.014
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide linkage study of bipolar disorder and co-morbid migraine: Replication of migraine linkage on chromosome 4q24, and suggestion of an overlapping susceptibility region for both disorders on chromosome 20p11

Abstract: Migraine and Bipolar Disorder (BPAD) are clinically heterogeneous disorders of the brain with a significant, but complex, genetic component. Epidemiological and clinical studies have demonstrated a high degree of co-morbidity between migraine and BPAD. Several genome-wide linkage studies in BPAD and migraine have shown overlapping regions of linkage on chromosomes, and two functionally similar voltage-dependent calcium channels CACNA1A and CACNA1C have been identified in familial hemiplegic migraine and recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 122 publications
(166 reference statements)
1
28
0
Order By: Relevance
“…The results of our study indicate that parental migraine, even in the absence of parental BD, is a risk factor for BD in the offspring. Therefore, our study provides epidemiological support for genetic studies indicating a genetic overlap between BD and migraine (Oedegaard et al, 2010a; Oedegaard et al, 2010b). However, the associations with BD found in our study were stronger for comorbid migraine than for parental migraine.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results of our study indicate that parental migraine, even in the absence of parental BD, is a risk factor for BD in the offspring. Therefore, our study provides epidemiological support for genetic studies indicating a genetic overlap between BD and migraine (Oedegaard et al, 2010a; Oedegaard et al, 2010b). However, the associations with BD found in our study were stronger for comorbid migraine than for parental migraine.…”
Section: Discussionsupporting
confidence: 71%
“…However, BD and migraine have pathophysiological similarities in terms of altered neurotransmission of dopamine (Cousins et al, 2009; Peroutka et al, 1997) and serotonin (Hamel, 2007; Mahmood and Silverstone, 2001). Genetic factors contribute greatly to the development of both BD and migraine, and genome-wide linkage and association studies have found overlapping regions between these two disorders (Oedegaard et al, 2010a; Oedegaard et al, 2010b). If the co-occurrence of BD and migraine is predominantly due to a genetic link between these disorders, then a familial clustering of BD and migraine would be expected.…”
Section: Introductionmentioning
confidence: 99%
“…While each of these results alone is interesting, their mapping to overlapping locations makes these results more compelling. Furthermore, the region of human chromosome 20 (HSA20) that is homologous to the segment of PHA10 containing this baboon QTL has been implicated in conditions such as restless legs syndrome (Levchenko et al 2006), migraine (Oedegaard et al 2010), and bi-polar disorder (Etain et al 2010). While the connection between these conditions and our baboon personality phenotypes may not be immediately obvious, dysregulation of the dopaminergic system is a suspected influence on each human phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The Xq27 region has now been implicated in migraine in three independent studies. Oedegaard and colleagues [18] conducted a genome-wide linkage study of bi-polar disorder and comorbid migraine using pedigrees derived from the National Institute of Mental Health (NIMH) Genetics Initiative for Bipolar Disorder. They identified a linkage peak with a LOD score of 1.6 (P00.003) in the Xq27 region (marker DXS9908 approx 1 Mb from DXS8043) that segregated with only the migraine and not the bipolar phenotype.…”
Section: Discussionmentioning
confidence: 99%